Ovarian Cancer Prevention, Screening, and Early Detection: Report From the 11th Biennial Ovarian Cancer Research Symposium. (1st November 2017) - Chien, Jeremy; Poole, Elizabeth M.
Abstract : Objective: The aim of this study is to provide a summary report on recent research advances in ovarian cancer prevention, screening, and early detection that were presented at the 11th Biennial Ovarian Cancer Research Symposium in Seattle, Wash. Methods: At the symposium, researchers from around the world participated in the poster, invited oral presentation and keynote presentation, and discussed the latest advances in the areas of cancer prevention, screening, and early detection. Results: In the Scientific Session for Prevention, Screening, and Early Detection, Usha Menon, PhD (University of College London), presented exploratory studies from the ongoing UK Collaborative Trial of Ovarian Cancer Screening trial. Karen Lu, MD, presented her studies on BRCA testing and salpingectomies as prevention strategies. Eight speakers were selected from the abstracts for short oral presentations, and the topic ranges from Ovarian Cancer Early Detection Program by Saul Rivkin, MD, to the ultra-deep sequencing of somatic mutations in TP53 in normal and cancer patients by Rosana Risques, PhD. Fourteen additional poster presentations, ranging from the potential role of cancer stem cells in recurrence to retrotransposons in ovarian cancer development, round up the session. Conclusions: Although progress is being made in the areas of prevention, screening, and early detection, these advances have not yet translated into tangible clinical benefits for patients with ovarian cancer. A wide array of research topics presented in the session provides a glimmer of hope that better understanding of genetic risk factors, refining screening strategies, and developing new methods for early detection will eventually lead to improved outcome for patients with ovarian cancer.